Integrating Character Building In English Language Teaching: A Comprehensive Exploration - Dyahningtyas, Eka Putri; Mardiana, Wiwik; Saifulloh, Ahmad Iklil (Philosophiamundi, 2024)
This research explores the values of character education based on the five main values of strengthening character education that are applied in the classroom. The method used in this research is qualitative. The sample for this research was one of the English teachers at SMP NEGERI 1 Mojosari. Data collection techniques are observation, interviews, and documentation. The results of this research show that teachers at SMP NEGERI 1 Mojosari have implemented 5 main values in strengthening character education, namely religious values, nationalism, integrity, independence, and mutual cooperation. These values have been implemented quite well in the teaching and learning process. Even though teachers at SMP NEGERI 1 Mojosari face obstacles, the school also continues to look for solutions to overcome these problems by strengthening teacher collaboration and fostering good relations between parents and SMP NEGERI 1 Mojosari.